APPRAISAL OF FINAL TAILINGS APPLICABILITY FOR PROCESSING AND PRODUCTION OF MODIFIERS OF IRON-CARBON ALLOYS - A. S. Panasugin; S. V. Grogorjev; V. A. Lomonosov; D. P. Mihalap; V. L. Tribushevskij; R. V. Degtjarev (Литьë и металлургия, 2011)
The methodology of rating of the galvanic final tailings applicability for further processing in the interests of needs of metallurgical production of the Republic Belarus is offered.